Peran Orang Tua Dalam Pendidikan Keagamaan Anak Usia Dini Di Lingkungan Keluarga Muslim - Muhamad Akip; Reni Aria Sari; Indah Winarni; Sirawati (STAI Bumi Silampari, 2025)
Religious education in early childhood plays a strategic role in shaping character, spirituality, and noble morals from an early age. In Muslim families, parents serve as the primary educators and role models in their children's daily lives. This study aims to examine the role of parents in providing religious education to early childhood children within Muslim households, the forms of their involvement, and the challenges they face. This research employs a descriptive qualitative approach using literature review methods sourced from nationally accredited academic journals published between 2019 and 2024. The findings reveal that parents contribute through exemplary behavior, habituation of worship practices, spiritual communication, and the use of Islamic-based educational media. However, several challenges persist, such as limited parental time, low religious literacy, and external influences that are not aligned with Islamic values. Recommended efforts include enhancing parents’ religious understanding through community religious forums (majelis taklim), increasing Islamic literacy, and fostering collaboration between families and educational institutions. This study affirms the critical importance of active parental involvement as the foundational pillar in instilling religious values and shaping morally upright and spiritually grounded Muslim children.